Serological and virological investigation of bovine viral diarrhea virus infection in cattle with abortion problem - Oya Bulut; Oguzhan Avci; Orhan Yapici; Orhan; Sibel Yavru; Atilla Simsek (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study is to determine the presence of Bovine Viral Diarrhea Virus (BVDV) infection in a cattle herd with abortion problem in Konya. Materials and Methods: Totally 228 blood serum and 228 leukocytes taken from cattle selected according to criteria for infertile and abortion problems were examined for antigens and antibodies to BVDV by Enzyme Linked Immunosorbent Assay. Results: In this research, 41 (17.9%) sera were found seropositive and 4 (1.7%) leukocytes were BVDV antigen positive. Of these 4 BVDV antigen positive cattle, a number of 2 (0.8%) were detected seropositive while 2 (0.8%) were seronegative. The animals being antigen positive and antibody negative were sampled second time after two weeks. The same results were detected for two seronegative cattle. The animals detecting persistent infection status were sent to slaughter. Conclusion: It is recommended that the animals should be checked in terms of BVDV for being negative both antigen and antibody before accepting them to the herds.